Īśvaraniṣṭhāñcyā pāūlakhuṇā: santāñce viṣayī adhika kāhī ... - Mañjūḷa, Vā. La. (Utkarṣa Prakāśana, 2008)
Articles on the life and works of various saints of Maharashtra, India; previously published in different Marathi magazines